Genetic Characteristics of Chloropsis cochinchinensis Gmelin, 1789 Based on The Mitochondrial DNA COI Gene - Jarulis Jarulis; Apin Saputra; Risky Hadi Wibowo (Jurnal Biodjati, 2023)
The rate of illegal poaching of blue-winged leafbirds (Chloropsis cochinchinensis) throughout Indonesia, particularly Bengkulu, is quite high. However, only minimal molecular information is available for this species. We performed mtDNA COI gene sequencing to explore genetic characters (conservative site, variable site, parsimony site, and singleton site) of blue-winged leafbirds. Using Qiagen's DNeasy® Blood and Tissue Kit based on the Spin-Column Protocol, total DNA was isolated, and PCR amplification methods were performed. DNA derived from a PCR reaction was forwarded to PT. First Base Malaysia for sequencing. Using MEGA 10.0 and BIOEDIT, the COI gene nucleotide sequence data were assembled, edited, and analyzed to explore of single nucleotide polymorphism, genetic distance, and phylogeny. The 616 bp COI genes contained 566 conservative sites (C), 50 variation sites (V), 24 information parsimony sites (Pi), and 26 singleton sites (S), as indicated by the results. The greatest nucleotide base composition was cytosine (34.1–34.9%), while the lowest was guanine (15.7–16.2%). The proportion of adenine-thymine nucleotide base pairs was greater than that of guanine-cytosine (50.3%). There were 26 barcode-specific mutation sites, 17 transition substitution mutation sites, and 9 transverse substitution mutation sites. The average genetic distance between C. cochinchinensis individuals was 2.2%, but the average genetic difference between species was 9.0%. All C. cochinchinensis individuals in our sample clustered within the same clade and were distinguished from other species within the same genus. The COI gene sequences of C. cochinchinensis that we acquired are novel and can be utilized for molecular identification of the species.